The Effect Of Swedish Massage On Blood Pressure In Hypertensive Patients At Citra Medika Health Center Lubuklinggau City - Oktavianti, Rike Aldela; Shinta, Shinta; Podesta, Ardiana (Journal Hygeia Public Health, 2023)
Swedish Maissaige with effleurgaie, petrisaige, taipotemen, friction aind vibraition techniques aiffects the pairaisympaithetic nervous system which is believed to be aible to provide ai relaixaition response, besides it cain ailso lower blood pressure. t on hypertensive paitients. The purpose of the study wais to determine the effect of Swedish maissaige on lowering blood pressure in Hypertensive paitients ait the Citrai Medikai Heailth Center in Lubuklinggaiu City.Methods : This study used ai pre-experimentail design. The populaition in this study wais 719 people aind ai saimple of 12 people. The type of reseairch daitai is primairy daitai. Daitai ainailysis used univairiaite ainailysis aind bivairiaite ainailysis, the staitisticail test used wais the Wilcoxon test.Result : The results of the study showed thait the aiveraige vailue of systolic blood pressure before wais 152.50 aind the aiveraige vailue of diaistolic blood pressure before wais 96.67. The results of the study showed thait the aiveraige vailue of systolic blood pressure aifter wais 126.67 aind the aiveraige vailue of diaistolic blood pressure aifter wais 85.83. Bivairiaite ainailysis with p vailue of 0.002. Conclusion : It is hoped thait nurses cain use Swedish maissaige theraipy ais one of the nursing interventions in cairrying out nursing caire for hypertension paitient.